2019
DOI: 10.3892/ol.2019.10551
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA HOTAIR promotes cancer cell energy metabolism in pancreatic adenocarcinoma by upregulating hexokinase‑2

Abstract: Hox transcript antisense RNA (HOTAIR) is a long non-coding RNA (lncRNA) that serves a key role in the pathogenesis of various types of cancer, including pancreatic adenocarcinoma. However, the diagnostic and prognostic values of HOTAIR in pancreatic adenocarcinoma, as well as its involvement in cancer cell energy metabolism, remain unclear. In the present study, tumor tissues and adjacent healthy tissues were collected from patients with pancreatic adenocarcinoma, and blood samples were collected from patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…Interestingly, mitochondrial TIGAR-HK2 complex upregulated HK2 and hypoxia-inducible factor 1 activity limiting reactive oxygen species production and protecting from tumor cell death under hypoxic condition implying that p53 could be an essential key regulator for HK2-mediated oncogenesis (26,30,48). In addition to signaling factors, HK2 regulated by epigenetic mediators including microRNAs (32,(52)(53)(54)(55), long non-coding RNAs (56)(57)(58), and histone/DNA methylation (59) are also important to modulate HK2-mediated tumorigenicity. Taken together, HK2 seems to be a master promoting factor in controlling carcinogenesis in different cancers; to date, however, the role of HK2 in controlling head and neck squamous cell carcinoma (HNSCC) development was rarely focused.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, mitochondrial TIGAR-HK2 complex upregulated HK2 and hypoxia-inducible factor 1 activity limiting reactive oxygen species production and protecting from tumor cell death under hypoxic condition implying that p53 could be an essential key regulator for HK2-mediated oncogenesis (26,30,48). In addition to signaling factors, HK2 regulated by epigenetic mediators including microRNAs (32,(52)(53)(54)(55), long non-coding RNAs (56)(57)(58), and histone/DNA methylation (59) are also important to modulate HK2-mediated tumorigenicity. Taken together, HK2 seems to be a master promoting factor in controlling carcinogenesis in different cancers; to date, however, the role of HK2 in controlling head and neck squamous cell carcinoma (HNSCC) development was rarely focused.…”
Section: Introductionmentioning
confidence: 99%
“…But recently, IncRNAs have been proved to be important regulators participating in the development of diseases, in particular cancer. 8,9 These lncRNAs could regulate the biological behaviors of tumor cells in terms of genomic stability, 10,11 transcription, 12,13 metabolism 14 and so on. Nevertheless, studies of lncRNAs in cancer are still at an early stage and need to be examined in more detail.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Common features of tumor metabolism include changes in glucose aerobic glycolysis, glutamine metabolism, tricarboxylic acid cycle, and anabolism, these characteristics may become a new development direction for the treatment of cancer, thereby avoiding and overcoming the genetic heterogeneity of tumors, and revealing the significance of research on the metabolism of substances in tumor cells. 32,33 Therefore, we previously performed a coexpression analysis of RP11-422N16.3 and a metabolic enzyme-related gene, and found that dimethylglycine dehydrogenase (DMGDH) was significantly positively correlated with RP11-422N16.3 expression, and low expression of DMGDH was a significant adverse factor in the prognosis of liver cancer patients. DMGDH has two splicing isoforms.…”
Section: Discussionmentioning
confidence: 99%